Evaluasi Penerapan dan Dampak Program Badan Usaha Milik Desa (BUMDES) Terhadap Kesejahteraan Masyarakat Rumah Tangga Miskin (RTM) di Desa Babadan Kecamatan Karangrejo Kabupaten Tulungagung (Periode Mei 2014–April 2015) - Dendhi Agung Nugroho (Universitas Negeri Malang, 2015)
The process of empowerment against poverty is a matter of humanity. The development of unbalanced cause social inequality, economic and political, both between countries, between regions, and between communities. Solving the problem of poverty should be based on a sound understanding of poor people themselves and their respect, protection and fulfillment of their basic rights.. With the guidance of Community Empowerment Board and Village Government (BPM-PD) Tulungagung, then on Monday, May 5th, 2014 formed village-owned enterprises (BUMDES)